Reflexiones de un adolescente que ejerce violencia: los hombres frente al feminismo - Reyes Ibarra, Vanessa Lilian; Figueroa Perea, Juan Guillermo (Pontificia Universidad Católica del Perú, 2023)
Using a case study, this paper focuses on the possibilities for a male adolescent to reflect, question and make ruptures on his own exercises of violence and on the interpellations he has experienced with women and feminism. Despite the negative consequences it entails, the repetition of rigid male gender roles and male mandates associated with violence, is often maintained as part of a male identity marked by dominance. However, gender socialization, as a process in continuous construction, opens the possibility for male adolescents to question the rigid learning acquired in childhood. It is concluded that adolescents who exercise violence can question themselves and break with previously acquired mandates associated with violence.

A partir de un estudio de caso, este trabajo se centra en las posibilidades que tiene un adolescente varón de reflexionar, cuestionar y hacer rupturas sobre sus propios ejercicios de violencia y sobre las interpelaciones que ha vivido con las mujeres y el feminismo. A pesar de las consecuencias negativas que conlleva, la repetición de los rígidos roles de género y de los mandatos masculinos asociados a la violencia suelen mantenerse como parte de una identidad masculina marcada por la dominación. Sin embargo, la socialización de género, como proceso en continua construcción, abre la posibilidad de que los adolescentes varones cuestionen el rígido aprendizaje adquirido en la infancia. Se concluye que los adolescentes que ejercen la violencia pueden cuestionarse a sí mismos y romper con los mandatos previamente adquiridos asociados con la violencia.
Reflections of an adolescent perpetrator of violence: Men and feminism
Keywords: Interpersonal violence; Adolescents; Masculinities; Feminism; Ruptures; Violencia interpersonal; Adolescentes; Masculinidades; Feminismo; Rupturas; https://purl.org/pe-repo/ocde/ford#5.04.03